Isolation and characterization of new antagonistic bacteria P10-7 and evaluation of its biocontrol potential against tomato gray mold - Chen, Denghui; Yue, Dandan; Li, Guanjie; Zhang, Zongyuan; Zhou, Liuzhu; Xu, Hongguang; Liu, Dehai; Wang, Xueyan (Frontiers in Microbiology, 2025)
Gray mold, caused by Botrytis cinerea, is one of the most destructive fungal diseases, causing significant losses in cash crops, especially tomatoes, worldwide. To address this challenge, we isolated and characterized a novel bacterial strain, P10-7, from tomato rhizosphere soil. Identification was performed using morphological, physiological, biochemical, and whole-genome sequencing analyses. The biocontrol potential of P10-7 was assessed through in vitro antagonism assays, analysis of secondary metabolites and lytic enzymes, and greenhouse pot experiments. Results showed that P10-7 was a strain of Bacillus amyloliquefaciens, with a total genome size of 3,929,792 bp, including 12 biosynthetic gene clusters. The antagonism test demonstrated broad-spectrum antifungal activity against seven fungal pathogens, including gray mold, with inhibition rates of 92.09% for mycelial growth and 98.03% for spore germination. Biochemical tests confirmed the strain’s ability to produce amylase, protease, pectinase, and siderophores. Furthermore, application of P10-7 cell suspension at 1.0 × 107 CFU/mL significantly promoted tomato seed germination and enhanced seedling growth (height, root length, fresh and dry weight). Critically, this treatment also markedly reduced disease incidence and effectively controlled tomato gray mold in greenhouse trials. Collectively, our findings demonstrate that Bacillus amyloliquefaciens P10-7 exhibits significant potential as an effective biocontrol agent against Botrytis cinerea.